Midventricular Obstructive Hypertrophic Cardiomyopathy during Pregnancy Complicated by Pulmonary Embolism: A Case Report - Leila Abid; Ahmed Tounsi; Dorra Abid; Mourad Hentati; Samir Kammoun (Case Reports in Medicine)
Hypertrophic cardiomyopathy (HCM) with midventricular obstruction (MVO) is a rare condition occurring in 1% of HCM patients. It is characterized by asymmetric left ventricular hypertrophy with MVO and elevated intraventricular pressure gradients. Pulmonary embolism has been associated with mid-ventricular obstructive HCM. Briefly, this case presents an unusual clinical scenario where a young pregnant woman suffering from hypertrophic obstructive cardiomyopathy presents with dyspnea hemodynamic compromise related to pulmonary embolism illustrating hemodynamic challenges created by pregnancy and surgery. We concluded that simple measures such as communication between the cardiology and obstetric teams, understanding of the hemodynamic changes, anesthetic planning, and monitoring were paramount for the success in our patient.